The Relationship between Bullying Behavior and Students' Social Interaction Ability - Khairul Anwar; Yeni Karneli (Jurnal Neo Konseling, 2020)
Social interaction is a dynamic reciprocal social relationship, which involves the relationship between individuals as individuals, between human groups, or between people and human groups. Good social interaction can prevent bullying behavior. Bullying is a form of violent behavior where there is psychological or physical coercion on a person or group of people who are "weaker" by a person or group of people who are more "strong". This study aims to reveal a description of the relationship between bullying behavior and the students' social interaction skills at SMA Negeri 8 Padang. This research is a descriptive correlational study, with a sample of 242 students obtained by using stratified random sampling technique. Stratified random sampling. The data collection instrument used a linkert-scale questionnaire which was compiled by itself in data collection using the google forms application. The results of this study indicate that (1) the bullying behavior of SMA N 8 Padang students is generally in the very low category of frequency 208 and percentage of 86%, low category of frequency 20 and percentage of 8.3%, medium category of frequency 13 and percentage of 5.4% , high frequency 1 category and percentage of 0.4%, meaning that students in SMA N 8 Padang in general can avoid bullying behavior, but there are still some students who do bullying; (2) the social interaction ability of SMA N 8 Padang students in general is in the medium category at 45%, 32% for high category, 21% for very high category, and 3% for low category. This means that students at SMA N 8 Padang generally have good social interaction skills, but there are still students who have poor social interaction skills; (3) there is a significant negative relationship between bullying behavior and students' social interaction abilities at SMA Negeri 8 Padang.